2011
DOI: 10.3155/1047-3289.61.7.786
|View full text |Cite
|
Sign up to set email alerts
|

Determining Seasonal Greenhouse Gas Emissions from Ground-Level Area Sources in a Dairy Operation in Central Texas

Abstract: Greenhouse gas (GHG) emissions from agricultural production operations are recognized as an important air quality issue. A new technique following the U.S. Environmental Protection Agency Method TO-14A was used to measure GHG emissions from ground-level area sources (GLAS) in a free-stall dairy operation in central Texas. The objective of this study was to quantify and report GHG emission rates (ERs) from the dairy during the summer and winter using this protocol. A weeklong sampling was performed during each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
0
13
2
Order By: Relevance
“…There would be location variation (cubicle or aisle zone) for CH 4 emission and manure height, but the averaged emission or depth of the whole open lot was less affected and relatively stable. other estimation based on field measurements by flux chamber in different dairy farms, the emissions estimated in our study were higher than the results from Misselbrook et al (2001) and lower than those from Borhan et al (2011aBorhan et al ( , 2011b, which were 3.5 g m −2 yr −1 or 4.6 kg hd −1 yr −1 for CH 4 and 0.13 g m −2 yr −1 or 1.4 kg hd −1 yr −1 for N 2 O, respectively. CO 2 emission was not available in the investigation of Misselbrook et al (2001), and it was 1588.6 kg hd −1 yr −1 according to Borhan et al (2011aBorhan et al ( , 2011b.…”
Section: Location Variation On Ghg Emissionscontrasting
confidence: 38%
See 2 more Smart Citations
“…There would be location variation (cubicle or aisle zone) for CH 4 emission and manure height, but the averaged emission or depth of the whole open lot was less affected and relatively stable. other estimation based on field measurements by flux chamber in different dairy farms, the emissions estimated in our study were higher than the results from Misselbrook et al (2001) and lower than those from Borhan et al (2011aBorhan et al ( , 2011b, which were 3.5 g m −2 yr −1 or 4.6 kg hd −1 yr −1 for CH 4 and 0.13 g m −2 yr −1 or 1.4 kg hd −1 yr −1 for N 2 O, respectively. CO 2 emission was not available in the investigation of Misselbrook et al (2001), and it was 1588.6 kg hd −1 yr −1 according to Borhan et al (2011aBorhan et al ( , 2011b.…”
Section: Location Variation On Ghg Emissionscontrasting
confidence: 38%
“…other estimation based on field measurements by flux chamber in different dairy farms, the emissions estimated in our study were higher than the results from Misselbrook et al (2001) and lower than those from Borhan et al (2011aBorhan et al ( , 2011b, which were 3.5 g m −2 yr −1 or 4.6 kg hd −1 yr −1 for CH 4 and 0.13 g m −2 yr −1 or 1.4 kg hd −1 yr −1 for N 2 O, respectively. CO 2 emission was not available in the investigation of Misselbrook et al (2001), and it was 1588.6 kg hd −1 yr −1 according to Borhan et al (2011aBorhan et al ( , 2011b. According to Misselbrook's investigation (2001), CH 4 and N 2 O emissions from dairy collecting or feeding yards were within 0.2~0.7 mg m −2 hr −1 and 2.9~39.3 μg m −2 hr −1 , respectively, when the ambient temperature was 5~25°C.…”
Section: Location Variation On Ghg Emissionscontrasting
confidence: 38%
See 1 more Smart Citation
“…Rahman et al (2013) found no difference in CH 4 flux rates or fluxes of beef cattle pen surfaces among months over a 7-mo study in North Dakota. Borhan et al (2011) found no effect of season on daily CH 4 emissions for a freestall dairy barn (manure lane and bedding area) and its loafing pen. Appuhamy et al (2016) reported that the IPCC (2006b) Tier 2 model, which the US EPA (2017a) methodology is based on, was associated with a notable mean bias for over-predicting enteric CH 4 emissions from lactating cows and thus was not ranked in the top 10 models for predicting enteric CH 4 emissions.…”
Section: Open-path Ch 4 Estimates Broadly Tracked Monthly Us Epa Estimentioning
confidence: 83%
“…Higher temperature in the summer accelerates GHG emissions from same anaerobic manure management operations than those in the winter with lower temperature. Previous research reported that the overall CH 4 and N 2 O ERs during the summer were approximately 5.3 and 2.2 times higher than those in the winter for a free-stall dairy in central Texas [40].…”
Section: Emission Comparison Based On the Usepa Recommendationmentioning
confidence: 85%